The influence of firm characteristics and corporate governance attributes towards intellectual capital reporting practices of companies listed on the main market of bursa Malaysia / Khadijah Sa'adah Zulkifli - Zulkifli, Khadijah Sa'adah (2019)
The right to control a company is a very valuable right since it provides the controlling party a numerous perk. These perks include both financial and non financial benefits such as power and prestige, expense accounts and many more. Therefore, this shall give concern to various stakeholders such as shareholders, employees, customers, suppliers, government, communities and groups of representing certain interest. Fama and Jensen's "The Separation of Ownership and Control" (1983) introduced the notion of agency theory that explained "the firm is seen as a nexus of contracts between individuals with vested interests, which created an equilibrium that can be accepted by all." The relationship between the management team including the chief executive officer (CEO) as agent and shareholders as principal lies when the principal provided the capital to the company so that agent can run the company. In return, the management team have a duty to fulfil their obligations in maximizing the shareholders' wealth. However, problems can occur in agency relationship whereby shareholders and the management team have different attitudes towards risk i.e. different interests and risk preferences. To ensure the agency problem is reduced, Jensen and Meckling (1976) proposed three control measures in which 1) monitoring costs, 2) bonding costs, and 3) residual costs. Nevertheless, this study shall focus on bonding costs in which it requires the management team to disclose relevant information i.e. financial and non-financial information that enables shareholders to monitor compliance with contractual agreements and to evaluate whether the management team have managed the firm's resources in the interest of shareholders. Since most companies disclosed financial information in their annual reports, which is mandatory in nature, the issue arises in determining the disclosure of non-financial information which is voluntary reporting. Therefore, this study aims to examine the level of intellectual capital reporting practice among 260 companies listed on Main Market of Bursa Malaysia. Securities Commission Malaysia (SC) has introduced the new amended Malaysian Code on Corporate Governance (MCCG) 2017 in addition to what has been spelt out under Bursa Malaysia's Listing Requirements (LR) to pave the way for an effective disclosure of non-financial information. This study is based on annual reports of the above said companies downloaded from Bursa Malaysia's website. Hence, this study suggested that two characteristics of a firm i.e. company size and leverage level can influence the level of intellectual capital reporting practice of listed companies. This study also suggested that two corporate governance attributes, i.e., CEO duality and board size can influence the level of intellectual capital reporting practice of listed companies. The findings of this study are expected to contribute to the literature work for future researchers' reference.